Social Justice and Deep Participation - Donnelly Roark, Paula. author. aut Link
XI, 228 p.
Keywords: Knowing what deep participation is, and how it works, can make a critical difference in solving 21st century economic, political, and social problems. This book provides a new approach to hands-on change and begins formulation of a participatory social theory promising greater prosperity and justice for all.